Masters of fashion illustration. - Downton, David (London : Laurence King, 2010)
With a foreword by the legendary model Carmen Dell’Orefice, the book follows the careers of Downton’s favourite artists, from the great social portraitist of the belle époque, Giovanni Boldini, to the architect of 1980s’ New Wave glamour, Tony Viramontes (including along the way such celebrated names as Erté, Carl Erickson, René Bouché, Andy Warhol and Antonio Lopez). The book concludes with a portfolio of David Downton’s own work, featuring drawings of the Paris haute couture shows and portraits of contemporary icons such as Dita Von Teese and Erin O’Connor. Many of the stunning images in Masters of Fashion Illustration have not been seen since they were first published.
boek